Guild boss - Castle, Jayne (A Harmony novel, 2021)
"TARGET CONSUMER: For fans of romantic suspense with a paranormal edge, and readers of J.D. Robb and Christine Feehan. A new novel in the futuristic paranormal series set on the earth colony Harmony by New York Times bestselling author Jayne Castle. Jayne Castle returns to Harmony in this installment of the bestselling series. CONTINUING THE ADVENTURE set in the world of Harmony"--